Summer English courses abroad versus 'at home'. (26th April 2014) - Serrano, Raquel; Tragant, Elsa; Llanes, Àngels
Abstract : The purpose of this study is to examine two L2 learning contexts (study abroad versus EFL intensive instruction at home) in terms of language development and learners' characteristics (including students' initial predisposition to learn English and their experience in the programme they enrolled in). Two groups of teenagers were considered: one group ( n = 58) received intensive classroom instruction for four weeks in their home country (Spain) and another group ( n = 54) spent a comparable amount of time abroad (United Kingdom), where they also attended language lessons. The learners performed two written tasks twice (at the beginning and at the end of their summer programme) and they filled in a questionnaire about their experience while studying. The results of our analyses suggest that, while the L2 develops in a comparable way in the two contexts, learners' characteristics and experiences are slightly different.